An investigation into the influence of female directors on audit effort: Evidence from FTSE 250 - Li, Yue (2013)
This study is conducted in order to detect if the female directors on board would have influence on the oversight function of the whole board and finally influence the audit fee. The motivation of this study is the increasing number of the female members in the workplace as well as the increasing number of female directors on board. This study focus on the UK market, so the data used in this paper is derived from FTSE 250 and the major methodology adopted in the empirical study is OLS regression method. The final results show that in UK market, the female directors cannot have that much influence on audit fees (the proxy of audit efforts), which shows different results from that in US market. Besides that, there is also other findings in this study, for example, the main determinants of the audit fee should be the operational and financial statistics of the company, the board characteristics cannot influence the audit efforts either.